Enhanced Photocatalytic Degradation Of Bisphenol A Under Visible Light Irradiation Using Nano Disc Rice Husk Ash Silica Templated Oxygen Doped Mesoporous Carbon Nitride And Carbon Dots Modified Graphitic Carbon Nitride - Bukola, Shittu Fatimah (2022)
A series of oxygen doped mesoporous carbon nitride (O-MCN) was synthesized via thermal polymerization method. Another series of carbon dots modified graphitic carbon nitride (CDs/g-C3N4) was also synthesized via microwave assisted thermal polymerization method. Both were used for the photodegradation of bisphenol A (BPA) under visible light irradiation. The O-MCN were labelled as xO-MCN ( x = 0.1, 0.2, 0.3, 0.4 and 0.5 g glucose) whereas the CDs/g-C3N4 were labelled as yCDs/g-C3N4 (y = 0.5, 1.0 and 1.5 ml CDs). The Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD) analysis, scanning electron microscopy (SEM), transmission electron microscopy (TEM), nitrogen adsorption-desorption (NAD), UV–vis diffuse reflectance spectroscopy (UV-vis DRS), photoluminescence (PL) spectroscopy, and X-ray photoelectron (XPS) spectroscopy were used to characterize the nanocomposites.